DOI: 10.1007/978-1-4020-8222-1_15
|View full text |Cite
|
Sign up to set email alerts
|

What is the Lowest Magnitude Threshold at Which an Earthquake can be Felt or Heard, or Objects Thrown into the Air?

Abstract: This article is a reflection on effects produced by earthquakes at both ends of intensity scales: II (‘Scarcely felt') and XII (‘Completely devastating'). Now that most seismic regions—at least in developed countries—are monitored by seismic networks with magnitude thresholds close to magnitude 1, less attention is paid to reports of abnormal phenomena such as vibrations or noises. The alleged reason is that, if the event has not been detected by monitoring networks, there was no event at all. This point of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This can be surprising for magnitudes that did not exceed 1.7. However, a recent study in the southern French Jura (Thouvenot and Bouchon, 2008) showed that earthquakes sited at a depth of c. 900 m could be felt even for negative magnitude values (down to magnitude −0.7). In Tricastin, as all relocated events but two have magnitudes larger than −0.7, and as focal depths are much shallower, practically all shocks could have been felt or – more probably – heard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be surprising for magnitudes that did not exceed 1.7. However, a recent study in the southern French Jura (Thouvenot and Bouchon, 2008) showed that earthquakes sited at a depth of c. 900 m could be felt even for negative magnitude values (down to magnitude −0.7). In Tricastin, as all relocated events but two have magnitudes larger than −0.7, and as focal depths are much shallower, practically all shocks could have been felt or – more probably – heard.…”
Section: Discussionmentioning
confidence: 99%
“…Piedmont seismic arc in Italy, is located 200 km to the east (Thouvenot and Fre´chet, 2006). The Provenc¸al domain of the Alpine belt begins just to the east of Tricastin, but the most active part of the orogen in terms of deformation and seismicity is located 150 km farther east.…”
Section: Introductionmentioning
confidence: 99%
“…Functioning as a single station, the Observatory array, in combination with other stations of the UK National Seismic Network, ensures that any earthquake near the site will be detected down to a magnitude slightly less than 2. However, smaller earthquakes than this can be felt (Thouvenot and Thouvenot and Bouchon, 2008), and a novel detection algorithm has been developed and implemented to utilise the five sensors in the vertical array (Luckett, 2021). This works using the principle that seismic waves from an earthquake will arrive at the bottom seismometer first.…”
Section: Seismic Monitoringmentioning
confidence: 99%
“…For instance, while we observe a mean drop of ~17% at the Ottawa station (ORIO) between the pre-lockdown and lockdown windows, the drop is actually double in the first few days immediately after the Province's lockdown announcement (Figure 5.2b). A change in the level of low-magnitude local seismicity, which is prevalent in the <1 s period band (McNamara & Buland, 2004), could be responsible for the relatively high late-stage noise levels (Thouvenot & Bouchon, 2008). This possibility cannot be ruled out especially in the Charlevoix seismic zone of eastern Canada where intraplate seismicity is not uncommon (e.g., Adams and Basham, 1989;Mazzotti and Adams, 2005).…”
Section: Variationsmentioning
confidence: 99%